The effect of musicality on language recovery after awake glioma surgery - Kappen, Pablo R.; van den Brink, Jan; Jeekel, Johannes; Dirven, Clemens M. F.; Klimek, Markus; Donders-Kamphuis, Marike; Docter-Kerkhof, Christa S.; Mooijman, Saskia A.; Collee, Ellen; Nandoe Tewarie, Rishi D. S.; Broekman, Marike L. D.; Smits, Marion; et al. (Frontiers in Human Neuroscience, 2023)
Awake craniotomy is increasingly used to resect intrinsic brain tumors while preserving language. The level of musical training might affect the speed and extend of postoperative language recovery, as increased white matter connectivity in the corpus callosum is described in musicians compared to non-musicians. In this cohort study, we included adult patients undergoing treatment for glioma with an awake resection procedure at two neurosurgical centers and assessed language preoperatively (T1) and postoperatively at three months (T2) and one year (T3) with the Diagnostic Instrument for Mild Aphasia (DIMA), transferred to z-scores. Moreover, patients’ musicality was divided into three groups based on the Musical Expertise Criterion (MEC) and automated volumetric measures of the corpus callosum were conducted. We enrolled forty-six patients, between June 2015 and September 2021, and divided in: group A (non-musicians, n=19, 41.3%), group B (amateur musicians, n=17, 36.9%) and group C (trained musicians, n=10, 21.7%). No significant differences on postoperative language course between the three musicality groups were observed in the main analyses. However, a trend towards less deterioration of language (mean/SD z-scores) was observed within the first three months on the phonological domain (A:-0.425/0.951 vs. B:-0.00100/1.14 vs. C:0.0289/0.566, p-value=0.19) with a significant effect between non-musicians vs. instrumentalists (A:-0.425/0.951 vs. B+C:0.201/0.699, p=0.04). Moreover, a non-significant trend towards a larger volume (mean/SD cm3) of the corpus callosum was observed between the three musicality groups (A:6.67/1.35 vs. B:7.09/1.07 vs. C:8.30/2.30, p=0.13), with the largest difference of size in the anterior corpus callosum in non-musicians compared to trained musicians (A:3.28/0.621 vs. C:4.90/1.41, p=0.02). With first study on this topic, we support that musicality contributes to language recovery after awake glioma surgery, possibly attributed to a higher white matter connectivity at the anterior part of the corpus callosum. Our conclusion should be handled with caution and interpreted as hypothesis generating only, as most of our results were not significant. Future studies with larger sample sizes are needed to confirm our hypothesis.